ÁFRICA(S), MOÇAMBICANIDADE, MIA COUTO: uma varanda para o Índico - Oliveira, Aluisio Barros de (2012)
Always seen by others eyes, unknown of the languages and other "realities" that constitute, the Africa, specially Mozambique, now (re)invent itself, palimpsestly, in narratives of your griots, narrators and/or storytellers. Our thesis intend, by the review of novel Under the frangipani, to demonstrate that the mozambican writer Mia Couto intends to participate the (re)construction of a devasted nation by war and conflicts, based on belief that the role writer "is to create requisites of a more african thought, to the assessment of your place and your time won't be done from categories created by others" (COUTO, 2005). At first, we show how the mozambican literary system consists itself; then, the insertion of coutian narrative against the prevalence tradition and, also, by the analysis of the constituent elements of the chosen novel, the way how made piece of resistance to reification, objectification of the individuald in the contemporary world , your writing will be present in this sharing of the sensitive. Besides Mia Couto, in our work we'll counting on the lessons of Candido, Noa, Hernandez, Adorno, Paz, Fonseca, Secco, among others studious of african narrative and, specially, Mozambique narrative